The discovery of androecia and sporophytes of the critically endangered Ascidiota blepharophylla C.Massal. (Porellaceae) in China and an assessment of its conservation status. (2nd October 2017) - Tang, Xia; Qian, Kai; Sun, Li-Wei; Zhang, Wei; Shi, Rui-Ping; Liu, Yun-Fei; Ji, Jia-Yue; Zhang, Xiao-Qing; Wang, Jian; Zhu, Rui-Liang
Abstract : Male plants and fertile populations of Ascidiota blepharophylla C.Massal. from Wanglang National Nature Reserve of Sichuan Province in China have been discovered recently. Here we present a description and illustrations of the androecia and sporophytes, and comment on the conservation status of this species.